Mesenchymal Stem Cells Early Response to Low-Dose Ionizing Radiation - Konkova, Marina; Abramova, Margarita; Kalianov, Andrey; Ershova, Elizaveta; Dolgikh, Olga; Umriukhin, Pavel; Izhevskaya, Vera; Kutsev, Sergey; Veiko, Natalia; Kostyuk, Svetlana (Frontiers in Cell and Developmental Biology, 2020)
Purpose of the study: to evaluate the effect of radiation doses 3, 10 and 50 cGy on human mesenchymal stem cell (MSC) cultures. Results: The effect of low-dose ionizing radiation (LDIR) on cell survival was studied. We investigated different LDIR effects on reactive oxygen species (ROS) production, DNA oxidation and DNA breaks. Using RT-PCR we determined expression of genes involved in the oxidative stress development (NOX4), antioxidative response (NRF2), anti– and proapoptotic mechanisms (BCL2, BCL2A1, BCL2L1, BIRC2, BIRC3, BAX). We studied the expression of genes responsible for the development of the nuclear DNA damage response, involved in repair complex and other repair processes (BRCA1, BRCA2). Activation of cell cycle genes transcription (CCND1, CDKN2A, CDKN1A), the number of proliferating MSC were analyzed using proliferation markers Ki-67 and PCNA antibodies. Conclusions: 10 cGy dose causes the strongest and fastest adaptive response following cell nuclei DNA damage. 3 cGy dose induces a less noticeable and prolonged adaptive effect. The maximal low range dose - 50 cGy, causes a strong damaging effect on the MSCs without a pronounced adaptive response..